Early Versus Late Effort in Dynamic Agencies with Unverifiable Information - Jens Robert Schöndube (BuR - Business Research, 2008)
In this paper we analyze a dynamic agency problem where contracting parties do not know the agent's future productivity at the beginning of the relationship. We consider a two-period model where both the agent and the principal observe the agent's second-period productivity at the end of the first period. This observation is assumed to be non-verifiable information. We compare long-term contracts with short-term contracts with respect to their suitability to motivate effort in both periods. On the one hand, short-term contracts allow for a better fine-tuning of second-period incentives as they can be aligned with the agent's second-period productivity. On the other hand, in short-term contracts first-period effort incentives might be distorted as contracts have to be sequentially optimal. Hence, the difference between long-term and short-term contracts is characterized by a trade-off between inducing effort in the first and in the second period. We analyze the determinants of this trade-off and demonstrate its implications for performance measurement and information system design.
urn:nbn:de:0009-20-16513
Keywords: 650; accounting; performance measurement; Prinzipal-Agent-Theorie; Vertragsrecht; Asymmetrische Information; Performance-Messung; Operations Research